(3GdCSeGA hGdUaGJs - (3CHh HcQ CMeO Hf GdMSjf Hf Ydj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s ((3CHh HcQ Hf CHj eMeO Hf CMeO GdMGhQGi s)
(3ChdgG (B:s
(3bGd GdTjN GdHjgbi QVi Gddg Yfg cJGH GSeGA Gddg Ld KfGhg hUaGJg GdJi Od cJGH Gddg SHMGfg hJYGdi Ydi EKHGJgG COhGJ YdjgG SfI QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3bGd NTjJc Ci QH bGd GSeYc QGgHG bGd GdTjN GdHjgbi QVi Gddg Yfg gPG BNQ eG Sgd Gddg JYGdi fbdg ai GSeGA Gddg JYGdi hUaGJg Je GdcJGH s
(3Cdag GdeDda dNRGfI TeS GdOjf CHj HcQ Hf YeQ GdGSOGHGPis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
Keywords: (3GdJhMjO hGdedd hGdfMds